Molecular dynamics of chemotactic signalling orchestrates dental pulp stem cell fibrosis during aging - Sun, Tianmeng; Zhong, Qing; Yu, Xiaoyi; Luo, Huanyu; Ren, Feilong; Liu, Cangwei; Chen, Peng; Flores-Borja, Fabian; Sun, Hongchen; An, Zhengwen (Frontiers in Cell and Developmental Biology, 2025)
Aging often triggers dental pulp fibrosis, resulting in clinical repercussions such as increased susceptibility to dental infections, compromised tooth vitality, and reduced responsiveness to dental interventions. Despite its prevalence, the precise molecular mechanisms underlying this condition remains unclear. Leveraging single-cell transcriptome analysis from both our own and publicly available datasets, we identified Ccrl2+ macrophages as particularly vulnerable during the early stages of aging. Notably, dental pulp progenitors with high expression of RARRES2, a unique ligand for CCRL2, facilitate the selective recruitment of a specific macrophage population to the stem cell niches. This process culminates in the formation of the ligand-receptor complex that engages CMKLR1, a receptor broadly expressed across macrophage populations. This interaction drives macrophage activation and expansion through the RARRES2/CCRL2/CMKLR1 axis. Through rigorous experimental validation, we demonstrated that macrophage activation and expansion within stem cell niches lead to increased secretion of proinflammatory factors, promoting dental pulp fibrosis during aging. Our findings uncover the intricate molecular dynamics of dental pulp aging, emphasizing immune microenvironment interactions. This study provides a novel perspective on potential therapeutic strategies for age-related pulp diseases by targeting macrophages and modulating the immune microenvironment.